2019
DOI: 10.1002/jia2.25271
|View full text |Cite
|
Sign up to set email alerts
|

Retest and treat: a review of national HIV retesting guidelines to inform elimination of mother‐to‐child HIV transmission (EMTCT) efforts

Abstract: Introduction High maternal HIV incidence contributes substantially to mother‐to‐child HIV transmission ( MTCT ) in some settings. Since 2006, HIV retesting during the third trimester and breastfeeding has been recommended by the World Health Organization in higher prevalence (≥5%) settings to reduce MTCT . However, many countries lack clarity on when and how often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 26 publications
(28 reference statements)
1
29
0
Order By: Relevance
“…In a recent review of 49 national HIV testing policies, 78% recommended repeat HIV testing. Eleven national guidelines did not include HIV retesting, including several countries identified as priority countries for PMTCT because of their high burden of HIV [45]. In settings where repeat HIV testing is prioritized, programmes should focus on missed opportunities for retesting (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent review of 49 national HIV testing policies, 78% recommended repeat HIV testing. Eleven national guidelines did not include HIV retesting, including several countries identified as priority countries for PMTCT because of their high burden of HIV [45]. In settings where repeat HIV testing is prioritized, programmes should focus on missed opportunities for retesting (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A recent paper reviewed and characterized the African countries' guidelines on the timing and frequency of maternal retesting. This study reported that in Kenya, South Africa, Tanzania, Uganda, Zambia, and Zimbabwe, regular retesting was part of the norm, but in other countries with a high rate of mother-to-child transmission, they were not consolidated [6].…”
Section: Plos Onementioning
confidence: 90%
“…Along the prevention of mother-to-child transmission (PMTCT) cascade, several ongoing challenges preclude reaching all women living with HIV and their HIV-exposed infants. In Mozambique, similar with the other priority countries in the African region [6], HIV testing is offered as per the WHO recommendations [7] at the ANCs and other mother and child health (MCH) services such as maternity wards, postpartum care clinics, and family planning clinics. However, systematic data collection on HIV retesting during the pregnancy-breastfeeding period in women with a previous negative test is not being performed.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-negative/uncertain versus HIV-positive women were more likely to attend ANC (93% vs. 81%; p < 0.001) and presented earlier for their first ANC visit (median gestation (IQR): 21 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) vs. 24 (18-35) weeks; p < 0.001) ( Table 1). At delivery, HIV status was confirmed in 75% of the entire cohort of whom 21% were positive.…”
Section: Participant Characteristicsmentioning
confidence: 99%